A small molecule drug promoting miRNA processing induces alternative splicing of MdmX transcript and rescues p53 activity in human cancer cells overexpressing MdmX protein - Valianatos, Georgios; Valcikova, Barbora; Growkova, Katerina; Verlande, Amandine; Mlcochova, Jitka; Radova, Lenka; Stetkova, Monika; Vyhnakova, Michaela; Slaby, Ondrej; Uldrijan, Stjepan (PloS one, 2017)
MdmX overexpression contributes to the development of cancer by inhibiting tumor suppressor p53. A switch in the alternative splicing of MdmX transcript, leading to the inclusion of exon 6, has been identified as the primary mechanism responsible for increased MdmX protein levels in human cancers, including melanoma. However, there are no approved drugs, which could translate these new findings into clinical applications. We analyzed the anti-melanoma activity of enoxacin, a fluoroquinolone antibiotic inhibiting the growth of some human cancers in vitro and in vivo by promoting miRNA maturation. We found that enoxacin inhibited the growth and viability of human melanoma cell lines much stronger than a structurally related fluoroquinolone ofloxacin, which only weakly modulates miRNA processing. A microarray analysis identified a set of miRNAs significantly dysregulated in enoxacin-treated A375 melanoma cells. They had the potential to target multiple signaling pathways required for cancer cell growth, among them the RNA splicing. Recent studies showed that interfering with cellular splicing machinery can result in MdmX downregulation in cancer cells. We, therefore, hypothesized that enoxacin could, by modulating miRNAs targeting splicing machinery, activate p53 in melanoma cells overexpressing MdmX. We found that enoxacin and ciprofloxacin, a related fluoroquinolone capable of promoting microRNA processing, but not ofloxacin, strongly activated wild type p53-dependent transcription in A375 melanoma without causing significant DNA damage. On the molecular level, the drugs promoted MdmX exon 6 skipping, leading to a dose-dependent downregulation of MdmX. Not only in melanoma, but also in MCF7 breast carcinoma and A2780 ovarian carcinoma cells overexpressing MdmX. Together, our results suggest that some clinically approved fluoroquinolones could potentially be repurposed as activators of p53 tumor suppressor in cancers overexpressing MdmX oncoprotein and that p53 activation might contribute to the previously reported activity of enoxacin towards human cancer cells.
Keywords: Female; Ofloxacin; Tumor Suppressor Protein p53; Breast Neoplasms; protoonkogenní proteiny c-mdm2; nádory prsu; DNA Damage; Ovarian Neoplasms; enoxacin; Signal Transduction; Humans; Enoxacin; ofloxacin; Melanoma; nádory vaječníků; proliferace buněk; lidé; apoptóza; down regulace; Cell Line, Tumor; melanom; Down-Regulation; alternativní sestřih; Alternative Splicing; ženské pohlaví; signální transdukce; Proto-Oncogene Proteins c-mdm2; poškození DNA; Cell Proliferation; Apoptosis; nádorový supresorový protein p53; nádorové buněčné linie